Zhuifeng tougu capsules inhibit the TLR4/MyD88/NF-κB signaling pathway and alleviate knee osteoarthritis: In vitro and in vivo experiments - Xu, Xiaotong; Li, Naping; Wu, Yongrong; Yan, Ke; Mi, Yilin; Yi, Nanxing; Tan, Xuyi; Kuang, Gaoyan; Lu, Min (Frontiers in Pharmacology, 2022)
Background: Knee osteoarthritis(KOA), a chronic degenerative disease, is mainly characterized by the destruction of articular cartilage and inflammatory reactions. At present, there is a lack of economical and effective clinical treatment. Zhuifeng Tougu (ZFTG) capsules have been clinically approved for the treatment of OA as it relieves joint pain and inflammatory manifestations. However, the mechanism of ZFTG in KOA remains unknown. Purpose: This study aimed to investigate the effect of ZFTG on the TLR4/MyD88/NF-κB signaling pathway and its therapeutic effect on rabbits with KOA. Study design: In vivo, we established a rabbit KOA model using the modified Videman method.In vitro, we treated chondrocytes with IL-1β to induce a pro-inflammatory phenotype and then intervened with different concentrations of ZFTG. Levels of IL-1β, IL-6, TNF-α, and IFN-γ were assessed with histological observations and ELISA data.The effect of ZFTG on the viability of chondrocytes was detected using a cell counting kit-8 and flow cytometry.The protein and mRNA expressions of TLR2, TLR4, MyD88, and NF-κB were detected using western blot and qRT-PCR, respectively to investigate the mechanism of ZFTG in inhibiting inflammatory injury of rabbit articular chondrocytes and alleviating cartilage degeneration. Results: The TLR4/MyD88/NF-κB signaling pathway in rabbits with KOA was inhibited, and the levels of IL-1β, IL-6, TNF-α, and IFN-γ in blood and cell were significantly down-regulated, consistent with histological results. The protein and mRNA expressions of TLR2, TLR4, MyD88, and NF-κB decreased in the ZFTG groups. Moreover, ZFTG promotes the survival of chondrocytes and inhibits the apoptosis of inflammatory chondrocytes. Conclusion: ZFTG alleviates the degeneration of rabbit knee joint cartilage, inhibits the apoptosis of inflammatory chondrocytes, and promotes the survival of chondrocytes.The underlying mechanism may be the inhibition of the TLR4/MyD88/NF-kB signaling pathway and secretion of inflammatory factors.